Kendrick's "Forward Integration Method" and the Dynamic Leontief Multisectoral Model - Kreijger, R. G.; Neudecker, H. (Quarterly Journal of Economics, 1976)
I. Introduction, 505—. II. The backward-looking system and Kendrick's system, 506.